2020
DOI: 10.1186/s13578-020-00432-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome-wide chromosome fusion and new gene birth in the Monopterus albus genome

Abstract: Background: Teleost fishes account for over half of extant vertebrate species. A core question in biology is how genomic changes drive phenotypic diversity that relates to the origin of teleost fishes. Results: Here, we used comparative genomic analyses with chromosome assemblies of diverse lineages of vertebrates and reconstructed an ancestral vertebrate genome, which revealed phylogenomic trajectories in vertebrates. We found that the whole-genome-wide chromosome fission/fusions took place in the Monopterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…There were multiple members of Dnmt3 in both mammals [ 32 ] and teleosts [ 33 ]. Two dnmt3a members ( dnmt3aa and dnmt3ab ) have been detected in the genome of Monopterus albus [ 34 ], which would be duplicated through whole-genome duplication event [ 35 ]. To further explore association of de novo DNA methylation with gonadal differentiation, we characterized transcription regulation of dnmt3aa and found that the transcription factor Foxa1 was responsible for transcriptional activation of dnmt3a gene.…”
Section: Discussionmentioning
confidence: 99%
“…There were multiple members of Dnmt3 in both mammals [ 32 ] and teleosts [ 33 ]. Two dnmt3a members ( dnmt3aa and dnmt3ab ) have been detected in the genome of Monopterus albus [ 34 ], which would be duplicated through whole-genome duplication event [ 35 ]. To further explore association of de novo DNA methylation with gonadal differentiation, we characterized transcription regulation of dnmt3aa and found that the transcription factor Foxa1 was responsible for transcriptional activation of dnmt3a gene.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, in the absence of SRY, ovary development will start via several female pathways. RSPO1/WNT signaling is a major pathway for ovary development, which includes RSPO1, WNT4B, CTNNB1 and GSK3A/B 7,8 . Mutations in these sex-determining genes and the dysregulation of relevant pathways will lead to DSDs, including 46,XY complete or partial gonadal dysgenesis, 46,XX testicular DSD, and 46,XX ovotesticular DSD.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many studies on new genes have focused on the model organisms including primates, rodents and Drosophila [1,[10][11][12][13]. However, there are few researches on new genes in non-model vertebrates, and no study using phylogenomic data has been conducted to investigate new genes in a lineage of teleosts [14]. In addition, teleosts usually have an additional genome-wide duplication event, compared to other vertebrates, which may result in more duplicate genes and some of them may have functions in these fishes [15,16].…”
Section: Introductionmentioning
confidence: 99%